Teori Percampuran dan Pertukaran - Sanurdi, Sanurdi (Tasamuh: Jurnal Studi Islam, 2019)
This discourse studies sociologically a syariah-based microfinance institute (LKMS) which is usually known as BMT. By applying the framework of new institutionalism, this dissertation utilizes qualitative approach in its data collection. This dissertation chose LKMS in Cipulir, Jakarta and Banda Aceh as its object of study because of socio-cultural and economic differences of both regions. This dissertation found that the profit and loss sharing system at the LKMS is regarded hybrid as it was previously adopted from traditional institution and recontextualized in a new meaning and certain condition. Theoretically, this hybrid mechanism will help traditional institutions become applicable and operational with the modern system of LKMS. This dissertation recommends the government to carry out a policy which is condusive to the development of microfinance institutions fitting with the local culture and religion. Establishment of Islamic banks is driven by the desire to avoid riba in Islamic muamalah activities, establish Islamic ukhuwah among Muslims as well as emotional and physical wellbeing gained through muamalah activities in accordance with religious orders that have ridlo of Allah SWT. This article discourse about that